Dinitrogen activation on graphene anchored single atom catalysts: local site activity or surface phenomena - Maibam, Ashakiran; Govindaraja, Thillai; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2019)
Catalysis on two-dimensional (2D) substrates with metal clusters or centers is generally dealt with as a surface phenomenon under the conjecture that the delocalized electron density is the driving force. When single atom catalysts (SACs) are anchored on such materials with delocalized electron density, for instance graphene, the stimulant for catalysis may be either the d-electrons on the metal or the system altogether. To understand the contributing factors of catalysis on such systems, a case study of dinitrogen (N-2) activation on Mo anchored graphene has been made by employing periodic and finite models of graphene. The periodic model represents a continuum of SACs anchored periodically on graphene, while the finite models are graphene nanoflakes of varying sizes and edge orientations. In addition to the physical aspects, such as size/finiteness of graphene, the influence of varying chemical compositions of the substrate on the activity is also evaluated by doping graphene with different B and N concentrations. This study, while clearly bringing out the connotation of regulating atomic composition of graphene substrate for dinitrogen activation, also surprisingly unveils the relative insignificance of varying the size and edge effects of the substrate. These features are highlighted through an analysis of red shift in the N-N stretching frequency, charge transfer to dinitrogen from the catalytic system, and structural and electronic characteristics of the catalytic system. The total and projected density of states plots reveal hybridization between the metal d orbitals and the p orbitals of carbon and nitrogen in the valence band. On the other hand, the frontier molecular orbital analysis also depicts a strong chemisorption of dinitrogen with the metal-graphene supports on account of direct hybridization between the d orbitals of the supported metal atom and the p orbitals of dinitrogen. The Bader and Lowdin charge distribution on the adsorbed dinitrogen in periodic and finite models shows the preeminence of local site over the surface activity.